Multiproduct competition, learning by doing and price-cost margins over the product life cycle: Evidence from the DRAM industry - Ralph Siebert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
In this study we specify and estimate a structural model of multiproduct firms for the semiconductor industry. In addition, we explicitly consider dynamics over the product life cycle. We find that these two aspects have important implications and provide evidence that (i) Spillover and Economies of Scale effects are lower for multiproduct firms than for single product firms, whereas Learning by Doing effects are slightly higher. We also find that firms follow an intertemporal output strategy. Furthermore, we provide evidence that, once multiproduct firms are introduced, firms behave as if in perfect competition. A single product specification leads to firms behaving even .softer. than Cournot players in the product market. We show that (ii) Learning by Doing, Economies of Scale, and Spillover effects vary over the product cycle. Learning by Doing effects are higher at the end of the life cycle when new production technologies are developed. Economies of Scale are increasing and become smaller (larger) over the life cycle for multiproduct (single product) firms. We specify a dynamic theoretical model and estimate a dynamic structural model by using quarterly firm-level output and costs data as well as industry prices for the Dynamic Random Access Memory (DRAM) industry from 1974 to 1996. – – In dieser Studie spezifizieren und schätzen wir ein strukturelles Modell von Mehrproduktunternehmen in der Halbleiterindustrie. Zusätzlich berücksichtigen wir explizit die Dynamik über den Produktlebenszyklus. Unsere Ergebnisse zeigen, daß diese beiden Aspekte gravierende Auswirkungen besitzen. Wir zeigen, daß (i) Spillovers und Skalenertr äge für Mehrproduktunternehmen geringer sind als für Einzelproduktunternehmen, wogegen Lerneffekte geringfügig größer ausfallen. Unsere Ergebnisse bestätigen auch, daß Unternehmen eine intertemporale Outputstrategie verfolgen. Weiterhin wird gezeigt, daß sich Mehrproduktunternehmen im perfekten Wettbewerb befinden, wobei sich Einzelproduktunternehmen ähnlich wie Cournot Spieler verhalten. Wir zeigen, daß (ii) Lerneffekte, Skalenerträge und Spillovereffekte über den Produktlebenszyklus variieren. Lerneffekte sind am Ende des Produktlebenszyklus größer, wenn neue Produkttechnologien entwickelt werden. Skalenerträge sind zunehmend und nehmen für Mehrproduktunternehmen (Einzelproduktunternehmen) im Ausmaß zum Ende des Produktlebenszyklus ab (zu). Wir spezifizieren ein dynamisches theoretisches Modell und schätzen ein dynamisches strukturelles Modell unter Verwendung von vierteljährlichen Output- und Kostendaten auf Unternehmensebene, von der .Dynamic Random Access Memory. (DRAM) Industrie für den Zeitraum von 1974 bis 1996.
Keywords: C1; L1; L6; O3; 330; Multiproduct Competition; Learning by Doing; Product Life Cycle; Economies of Scale; Spillovers; Semiconductor; Process Innovation; Mehrproduktunternehmen; Lerneffekte; Produktlebenszyklus; Skalenerträge; Spillovers; Halbleiterindustrie; Prozeßinnovationen